Семиотический анализ автобиографического нарратива Марины Цветаевой – возможности и ограничения - Dorota Jewdokimow (Avtobiografija, 2020)
A large part of Marina Tsvetaeva’s journals describes her years in Moscow immediately after the 1917 revolution. Tsvetaeva divides her post-revolutionary experiences into two separate spheres: internal life, being (byt’e) and external life, existence (byt), where internal life is valued positively, while external life is assessed negatively or neutral. The sphere of existence, in Tsvetaeva’s testimony, constitutes the essence of the revolution. The main aim of this article is the description of this sphere, with the simultaneous definition of its relationship with being. Another goal is to define the boundaries of the semiotic analysis of an autobiographical text and the possibility of a pre-text experience, that exists prior to the text. In Tsvetaeva’s text, I distinguish those fragments that refer directly to her individual experience of a revolution located in the area of individual emotionality. Determining to what extent the emotional experience is physiological and therefore pre-discursive, and to what extent cultural and therefore discursive, will depend on the possibility of its semiotic analysis.